The Relationship Between Preoperative Feeding Exposures and Postoperative Outcomes in Infants With Congenital Heart Disease. Issue 1 (January 2021) - Kataria-Hale, Jasmeet; Cognata, Acacia; Hagan, Joseph; Zender, Jill; Sheaks, Paige; Osborne, Scott; Roddy, Jeramy; Hair, Amy
Abstract : Objectives: To evaluate the association of preoperative risk factors and postoperative outcomes in infants with complex congenital heart disease. Design: Single-center retrospective cohort study. Setting: Neonatal ICU and cardiovascular ICU. Patients: Infants of all gestational ages, born at Texas Children's Hospital between 2010 and 2016, with complex congenital heart disease requiring intervention prior to discharge. Interventions: None. Measurements and Main Results: A total of 399 patients were enrolled in the study. Preoperative risk factors included feeding, type of feeding, feeding route, and cardiac lesion. Postoperative outcomes included necrotizing enterocolitis, hospital length of stay, and days to full feeds. The occurrence rate of postoperative necrotizing enterocolitis (all stages) was 8%. Preoperative feeding, type of feeding, feeding route, and cardiac lesion were not associated with higher odds of postoperative necrotizing enterocolitis. Cardiac lesions with ductal-dependent systemic blood flow were associated with a hospital length of stay of 19.6 days longer than those with ductal-dependent pulmonary blood flow ( p < 0.001) and 2.9 days longer to reach full feeds than those with ductal-dependent pulmonary blood flow ( p < 0.001), after controlling for prematurity. Nasogastric feeding route preoperatively was associated with a length of stay of 29.8 days longer than those fed by mouth ( p < 0.001) and 2.4 days longer to achieve full feeds ( p < 0.001), after controlling for prematurity and cardiac lesion. Preoperative diet itself was not associated with significant change in length of stay or days to reach full feeds. Conclusions: Although cardiac lesions with ductal-dependent systemic blood flow are considered high risk and may increase length of stay and days to achieve full feeds, they are not associated with a higher risk of postoperative necrotizing enterocolitis. Nasogastric route is not associated with a significantly higher risk of necrotizing enterocolitis, but longer length of stay and days to reach full feeds. These findings challenge our perioperative management strategies in caring for these infants, as they may incur more hospital costs and resources without significant medical benefit. Abstract : Supplemental Digital Content is available in the text.